2004
DOI: 10.1111/j.1755-6686.2004.tb00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Care for Dialysis Patients in Japan

Abstract: In Japan, the number of chronic renal failure patients requiring dialysis treatment is increasing by approximately 10,000 patients a year, totalling 229,538 or 1,801.2 patients per one million population at the end of December, 2002 according to the survey conducted by the Japanese Society for Dialysis Therapy. The primary disease is diabetic nephropathy (28.1% of patients), and with greater numbers of long-term and elderly patients, the incidence and severity of complications continue to increase. Dialysis un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…In spite of the favourable comparison with hospital nursing, this indicates that the quantitative demands are in need of improvement. Many studies show clearly that quantitative demands are a critical issue, particularly in the context of staff reductions [5,17] or limited number of staff [10,26]. As for the emotional demands, the hospital nurses rated this aspect considerably higher than the other two professional groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In spite of the favourable comparison with hospital nursing, this indicates that the quantitative demands are in need of improvement. Many studies show clearly that quantitative demands are a critical issue, particularly in the context of staff reductions [5,17] or limited number of staff [10,26]. As for the emotional demands, the hospital nurses rated this aspect considerably higher than the other two professional groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dialysis employees rated their influence and the degree of freedom as being significantly lower than did hospital nurses, thus a compensation of the relatively high demands by high control or support is not given. An obvious conclusion is that the standardized work processes allow little possibility of influencing the work; the employees themselves described their work as routine [17]. Other studies also have shown that dialysis staff would like to be more actively involved in the decision making process [1,17,29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations